Robust DC motor system and speed control using genetic algorithms with two degrees of freedom and h infinity control - Chitsanga, N.; Kaitwanidvilai, S. (My University, 2017)
This paper presents a new design controller called "Robust and fixed-structure 2DOF control" for a DC motor and speed control system. The controller is designed using the concept of 2DOF control with robust loop shaping. The specification of time domain includes in the controller design by using the reference model. Moreover, the structures of both pre-filter and feedback controllers are fixed as a simple structure to make the system robust and still useful in practical works. Instead of solving mathematically complicated equations, Genetic Algorithm is proposed to solve the process of the design control problem. The proposed control is implemented in a speed control of DC Motor. As seen in the results, the proposed system performs better performance, compared to the 1DOF Fixed Structure control and Robust Loop Shaping Control. When the system payloads are changed from 0 kg to 16 kg, the step response from the conventional 1 DOF controller is oscillated obviously at 16 kg., while the proposed controller performs the smooth and stable response.
Keywords: 2DOF H infinity Control; DC motor system; Fixed-Structure control and Robust Control; Genetic algorithm